New findings on Dendrobranchiata fossils of the Romualdo Formation, Araripe Basin, Northeast of Brazil - Alencar, Damares Ribeiro; de Oliveira, Gustavo Ribeiro; Pinheiro, Allysson Pontes; Saraiva, Antônio Álamo Feitosa (Zootaxa, 2020)
The Araripe Basin is the largest inland basin in northeastern Brazil is known for its preservation excellent, number of specimens and variety of fossil species. The Araripe Basin stands out for its fossiliferous content of well known fossil groups, from vertebrates to invertebrates, especially decapod crustaceans. Thus, a morphological re-description of two shrimp species, Paleomattea deliciosa and Araripenaeus timidus, was carried out through taxonomic and morphoanatomical analysis. The mechanical preparation methodology was adopted in the laboratory, with a total of 58 specimens were analyzed and photographed to determine which characters were preserved or not, as well as to compared these with holotypes. The results show that characters such as carapaces complete with the presence of spines, pleon with six somites, pereiopods and pleopods, in addition to uropods and telson were preserved in Paleomattea deliciosa, while carapaces, pleon complete and pereiopods were preserved in Araripenaeus timidus. Thus, the current study provides new species information which can be used in future species-type studies and contributes to a better understanding of these Araripe species.